The Construction of A Multi-epitope Vaccine Against Klebsiella pneumoniae Using in silico Approach - Wonggo, Dhammiko; Wahjudi, Mariana (Cell and BioPharmaceutical Institute, 2023)
Background: Klebsiella pneumoniae is one of the bacteria that causes pneumonia infection. Even though the number of pneumonia cases is relatively high and has become a global problem, there is still no vaccine available to prevent this disease. This study was aimed to design a multi-epitope vaccine design through an in silico approach, against K. pneumoniae.Materials and method: Vaccine candidate was constructed based on proteins of K. pneumoniae. These proteins were analyzed to identify the antigens sequence for multi-epitope vaccine design. The constructed vaccine was predicted for allergenicity, toxicity, population coverage, and its physicochemical properties. The vaccine structure was then docked with the toll like receptor 2 (TLR2) molecule to show the interaction. Expression analysis and cloning of the constructed vaccine was carried out in the pET-28a vector using SnapGene.Results: The vaccine was 567 amino acids long, consisting of Cholera Toxin Subunit B as an adjuvant, 6 B-cell epitopes, 11 cytotoxic T-cell epitopes, and 10 helper T-cell epitopes connected with the appropriate linker. Epitopes analysis showed that the vaccine will be a non-toxic, has high antigenicity, but non-allergenic. The vaccine was predicted to be stable, hydrophilic, and had a low risk of triggering autoimmune response. The vaccine molecule was compatible to humans TLR2 molecule. Furthermore, visualization of the candidate vaccine protein on pET-28a showed that the vaccine protein might be expressed correctly.Conclusion: The construction of multi-epitope vaccine has been developed, which might be a good vaccine candidate, containing 6 B-cell epitopes, 11 CTL epitopes, and 10 HTL epitopes. The construct may help scientists to experimentally formulate multi-epitope vaccine against K. pneumoniae in the future.Keywords: in silico, Klebsiella pneumoniae, multi-epitope, vaccine